Reliability measurement and ICD-10 validation of ICPC-2 for coding/classification of diagnoses/health problems in an African primary care setting. (17th January 2018) - Olagundoye, Olawunmi A; Malan, Zelra; Mash, Bob; van Boven, Kees; Gusso, Gustavo; Ogunnaike, Afolasade
Abstract: Background: The routine application of a primary care classification system to patients' medical records in general practice/primary care is rare in the African region. Reliable data are crucial to understanding the domain of primary care in Nigeria, and this may be actualized through the use of a locally validated primary care classification system such as the International Classification of Primary Care, 2nd edition (ICPC-2). Although a few studies from Europe and Australia have reported that ICPC is a reliable and feasible tool for classifying data in primary care, the reliability and validity of the revised version (ICPC-2) is yet to be objectively determined particularly in Africa. Objectives: (i) To determine the convergent validity of ICPC-2 diagnoses codes when correlated with International Statistical Classification of Diseases (ICD)-10 codes, (ii) to determine the inter-coder reliability among local and foreign ICPC-2 experts and (iii) to ascertain the level of accuracy when ICPC-2 is engaged by coders without previous training. Methods: Psychometric analysis was carried out on ICPC-2 and ICD-10 coded data that were generated from physicians' diagnoses, which were randomly selected from general outpatients' clinic attendance registers, using a systematic sampling technique. Participants comprised two groups of coders (ICPC-2 coders and ICD-10 coders) who coded independently a total of 220 diagnoses/health problems with ICPC-2 and/or ICD-10, respectively. Results: Two hundred and twenty diagnoses/health problems were considered and were found to cut across all 17 chapters of the ICPC-2. The dataset revealed a strong positive correlation between selected ICPC-2 codes and ICD-10 codes ( r ≈ 0.7) at a sensitivity of 86.8%. Mean percentage agreement among the ICPC-2 coders was 97.9% at the chapter level and 95.6% at the rubric level. Similarly, Cohen's kappa coefficients were very good ( κ > 0.81) and were higher at chapter level (0.94–0.97) than rubric level (0.90–0.93) between sets of pairs of ICPC-2 coders. An accuracy of 74.5% was achieved by ICD-10 coders who had no previous experience or prior training on ICPC-2 usage. Conclusion: Findings support the utility of ICPC-2 as a valid and reliable coding tool that may be adopted for routine data collection in the African primary care context. The level of accuracy achieved without training lends credence to the proposition that it is a simple-to-use classification and may be a useful starting point in a setting devoid of any primary care classification system for morbidity and mortality registration at such a critical level of public health importance.